Pengembangan Game Karambol Pada Interactive Projected Display - Bima Tri Atmaja; Eriq M. Adams Jonemaro; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Carrom is a game that uses square-shaped table with four holes in each corner of the diagonal, with the tools of the game in the form of coins carrom. This game uses small discs instead of balls. The driving force is the finger shifted on the disc so hit the target. Players must put all the coins carrom into the hole located at the corner of the board. Otherwise the player wins if one of player put all the pieces carrom coins faster than other players. Carrom games will be developed into a more modern technologies. Carrom games are displayed via a projector using Ubi Displays technology (Interactive Projected). Ubi Displays a prototype toolkit using a projector and Kinect, where the game can be displayed and played on types of surfaces as on wall. From the test results of students in Islamic Junior High School Wahid Hasyim 01 Dau showed that carrom game is well received. This can be seen from more than 67% of students in Islamic Junior High School said this game interesting, because according from the students of Islamic Junior High School packed game in a new form using the interactive projected display which all surfaces into a touch screen game, so the game looks real (like the original game).